2012
DOI: 10.1002/jbio.201100120
|View full text |Cite
|
Sign up to set email alerts
|

In‐vivo Tumor detection using diffusion reflection measurements of targeted gold nanorods – a quantitative study

Abstract: The ability to quantitatively and non-invasively detect nanoparticles has important implications on their development as an in-vivo cancer diagnostic tool. The Diffusion Reflection (DR) method is a simple, non-invasive imaging technique which has been proven useful for the investigation of tissue's optical parameters. In this study, Monte Carlo (MC) simulations, tissue-like phantom experiments and in-vivo measurements of the reflected light intensity from tumor bearing mice are presented. Following intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 35 publications
0
87
0
Order By: Relevance
“…By reducing the laser irradiation, GNP-targeted cancer cells can be detected without affecting cell viability. It has been shown that a low concentration of GNPs (0.02 mg/mL), lower than that found in several in vivo studies, 18,32,33 can be easily detected. An important advantage of this imaging technique is the use of the absorption properties of GNPs rather than their scattering properties, leading to high contrast between targeted cancer cells and normal background tissue.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…By reducing the laser irradiation, GNP-targeted cancer cells can be detected without affecting cell viability. It has been shown that a low concentration of GNPs (0.02 mg/mL), lower than that found in several in vivo studies, 18,32,33 can be easily detected. An important advantage of this imaging technique is the use of the absorption properties of GNPs rather than their scattering properties, leading to high contrast between targeted cancer cells and normal background tissue.…”
Section: Resultsmentioning
confidence: 74%
“…In addition, it can be seen that there was a positive correlation between the gold nanorod concentrations and temperature elevation. For the highest gold nanorod concentration (0.1 mg/mL), a temperature difference of about 14°C was observed after 10 seconds of irradiation, while for the lowest detectable concentration (0.02 mg/mL), a concentration that is clinically relevant, 12,18,30 the temperature was elevated by about 1°C after the same period of time.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…One slide was stained with hematoxylin and eosin (H&E) and evaluated by a pathologist for tumor borders. The other was de-paraffinized, marked with the tumor borders identified on the H&E-stained slide, and stained with anti-EGFR antibody conjugated to GNPs, as previously described [13,14].…”
Section: Immunostaining With Ant-egfr Conjugated To Gnpsmentioning
confidence: 99%
“…The GNPs were bioconjugated to EGFR-expressing head and neck cancer cells. The accumulation of the GNPs in the cancer cells caused an increase in their absorption properties, resulting in a specific reflection signal of the tumor site [14,15].…”
Section: Introductionmentioning
confidence: 99%